Litigating Salvation: Race, Religion and Innocence in the Karla Faye Tucker and Gary Graham Cases - Price, Melynda J. (2006)
The cases of Karla Faye Tucker and Gary Graham represent two examples of the renewed public debate about the death penalty in the State of Texas, and how religion and race affect that debate. This article explores how the Tucker and Graham cases represent opposing possibilities for understanding contemporary narratives of the death penalty. Though the juxtaposition of these two cases is not completely symmetrical, if viewed as a kaleidoscope—a complex set of factors filtered through the shifting identities of the person who is at the center of the immediate case—the hidden operations of race and religion can be examined. Tucker and Graham, both prosecuted in Houston's Harris County and executed in relatively close proximity, demonstrate the function that race, religion and gender play in current death penalty politics. Thus, the death penalty cases of Karla Faye Tucker and Gary Graham inform an understanding of the intersection of race and gender in current death penalty narratives and the connection of those narratives to past tropes employed to justify the use of the death penalty, in spite of its discriminatory impact on blacks. In attempting to untangle the continuing impact of race and gender, the increased reliance on religious narrative can be understood in relation to the pro-death penalty arguments of the past. These simple syllogisms, constructed above in the words of Karla Faye Tucker and George W. Bush, logically demonstrate how individual opinions on the death penalty can work in different cases. However, the peculiarity of the supporters who came forward to ask for mercy in Tucker's case contradicts the idea that, at least for some, the identity of the defendant has no bearing on whether one supports or opposes the death penalty. Commentator Julie H. Patton objected to the emphasis on Karla Faye Tucker's gender instead of what she perceived to be the more important issue: the inherent evil of capital punishment. Patton predicted, “The protester who supported her [Tucker's] clemency because of her religious conversion will most likely not be there when the next inmate is walked to the death chamber.” The cases of Tucker and Graham broke rank and captured the attention of both individual citizens as well as political and religious elites. However, the citizens, political and religious elites were not the same in the two cases, race being the clearest distinction. This article compares the Tucker and Graham cases and attempts to position them as opposing ends of a spectrum of possibilities of how religion may extend historical race and gender narratives into the present. By setting these cases at odds and adopting narratives that overlap gender and racial narratives, this article attempts to illuminate ways in which these cases help us understand how death row inmates may be able to rehabilitate themselves and, in a sense, cleanse their personas as if they were innocent. The reliance that contemporary narratives place on religion actually obscures or reiterates the more obvious racial and gendered character of past narratives to justify the death penalty. Religion is the new language of the death penalty, but it is not divorced from the old